Reading the Miller's Tale Reading the Miller's Tale - Valerie Edden (Ilha do Desterro, 2008)
Modern narrative theory has provided new ways of analysing
stories and a new critical vocabulary for discussing narratives.
Some such theories emphasise the way in which the reader is involved in the act of reading a narrative, bringing skills and assumptions to the text which enable him to interpret the ords which make up the story. Traditionally we have tended to onfine literary analysis to the words on the page; arratologists and structuralists invite us to examine also what the reader brings to the text. Such an analysis not only nterprets the texts under discussion but also helps to lay bare the assumptions of the reader. This paper will provide an analysis of Chaucer's Miller's Tale using a theory of narrative analogous with transformational grammar.